Transboundary Haze: Islam Prohibits Destruction of Earth - Md Sofwan, Nurzawani; Mahidin, Hartini; Tambi, Edmund Shah (Pascasarjana IAIN Pontianak, 2018)
Recurring episodes of transboundary haze have been similarly to an annual event in Malaysia since the 1980’s. Transboundary haze is typically haze caused by forest fires in Sumatra and Kalimantan, Indonesia which moves thousands of miles and encompasses neighboring regional countries. This is caused by human hands that continue to pursue unplanned development without taking into account the aspect of environmental sustainability. This study looks into and the understanding of recurring occurrences of transboundary haze in Sarawak. From the perspective of Islam, by making the Holy Quran as the absolute source of reference, God forbids the destruction of nature and calls upon mankind to do good not only to other humans and animals but also to the environment. Human beings are endowed with a great mind that can guide them to make and do the right thing, thus, various efforts need to be taken into consideration and be done collectively amongst the ASEAN countries in a joint effort towards reducing or preventing continuous episodes of transboundary haze within the region.